Durrell Writing about Writers Writing: Towards a Spatial Definition of "The Avignon Quintet" - Ramón Plo Alastrué (Miscelánea: A Journal of English and American Studies, 1996)
The aim of this paper is to analyze the reciprocal influence between Lawrence Durrell and the fictional writers he creates in The Avignon Quintet . In order to explore this blurring of boundaries between fiction and reality, I reflect on the confluence of two opposite forces at work in these novels: the Quintet both acknowledges its own status as fiction and gradually increases the feeling of proximity to a random, ineffable reality. Throughout this paper, I shall also try to interpret the shape of the quincunx and its three-dimensional development—the pyramid—as the narrative architecture where these two antagonistic ideas are condensed into a single process of creation.